Initial Arrival and Transitional Experiences of International Students at a U.S. University - Sharma, Reeti (Journal of International Students, 2026)
The globalization of higher education has increased cross-cultural educational exchanges. As international students navigate their new environment, they face numerous challenges. Challenges during the transitional phase are especially critical as they diminish their sense of mattering and marginalize. This qualitative study explores the initial arrival experiences of eleven international students at a public university in the U.S. through the lens of the theory of marginality and mattering. This phenomenological study’s findings reveal that international students’ transitional challenges included issues related to housing, food, and transportation. Their sense of mattering is not linear and is highly dependent on specific spaces, recognition from staff and educators, and relationships with peers. Overall, the findings indicate that the adjustment of international students is situational and requires sustained, institutionally tailored support. Lack of this support marginalizes them, diminishing their sense of worthiness and negatively impacting their academic experience in the U.S.